Digital breast tomosynthesis technique and cases - Barkhausen, Jörg; Rody, Achim; Schäfer, Fritz K. W. (Thieme, 2016)
"This book is an authorized translation of the German edition published and copyrighted 2015 by Georg Thieme Verlag, Stuttgart. Title of the German edition: Digitale Tomosynthese der Brust."